Video art : a guided tour - Elwes, Catherine, 1952- (I.B. Tauris ; in association with University of the Arts ; In the United States of America and in Canada distributed by Palgrave Macmillan, 2005)
Video art dominates the international art world to such an extent that its heady days on the radical fringes are sometimes overlooked - often unknown. This text is a guide to video art and its history, tracing the story from the weighty Portapak equipment of the '60s and '70s to today's digital technology.
Keywords: Video art.; Art, Modern -- 20th century.; Art, Modern.; Art vidéo.; Art -- 20e siècle.; video art.; ART -- Mixed-Media.; Art, Modern; Video art; Videokunst.; 1900-1999